2006
DOI: 10.1152/jn.00582.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Systems Analysis of the Control of Burst Duration by Low-Voltage-Activated Calcium Current in Leech Heart Interneurons

Abstract: Olypher, Andrey, Gennady Cymbalyuk, and Ronald L. Calabrese. Hybrid systems analysis of the control of burst duration by low-voltage-activated calcium current in leech heart interneurons. J Neurophysiol 96: 2857-2867. First published August 30, 2006 doi:10.1152/jn.00582.2006. The leech heartbeat CPG is paced by the alternating bursting of pairs of mutually inhibitory heart interneurons that form elemental half-center oscillators. We explore the control of burst duration in heart interneurons using a hybrid sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…Previous studies in other systems have suggested that the h -current might counteract the hyperpolarizing effects of the pump current (e.g., Robert and Jirounek, 1998; Soleng et al, 2003; Baginskas et al, 2009). Moreover, Hill et al (2001) developed a canonical model of the oscillator heart interneurons and showed that increasing the h -current conductance decreases the period, which was later supported by dynamic clamp experiments (Sorensen et al, 2004; Olypher et al, 2006). Using a hybrid half-center oscillator, Sorensen et al (2004) found that increasing the h -current conductance of living or silicon neurons with dynamic clamp decreases the period and interburst interval, without affecting the burst duration.…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies in other systems have suggested that the h -current might counteract the hyperpolarizing effects of the pump current (e.g., Robert and Jirounek, 1998; Soleng et al, 2003; Baginskas et al, 2009). Moreover, Hill et al (2001) developed a canonical model of the oscillator heart interneurons and showed that increasing the h -current conductance decreases the period, which was later supported by dynamic clamp experiments (Sorensen et al, 2004; Olypher et al, 2006). Using a hybrid half-center oscillator, Sorensen et al (2004) found that increasing the h -current conductance of living or silicon neurons with dynamic clamp decreases the period and interburst interval, without affecting the burst duration.…”
Section: Resultsmentioning
confidence: 84%
“…I CaS drives the burst phase slowly inactivating to release, as spike rate wanes, the opposite inhibited neuron of the half-center oscillator, while the I h activated by the hyperpolarization associated with inhibition, which also removes inactivation from I CaS ), drives the inhibited neuron of the HCO toward escape and burst formation. This mixed escape-release model for rhythmicity in a half-center microcircuit has been repeatedly corroborated by modeling [29,3436] and dynamic-clamp studies [37,38]. The endogenous peptide myomodulin speeds the burst rhythm of the two HCOs by up-modulating I h and down modulating the current driven by the Na + /K + pump [39].…”
Section: Leech Heartbeatmentioning
confidence: 78%
“…Previous studies of this HCO model and electrophysiological studies of the leech heartbeat have addressed fundamental questions about the mechanism of bursting [4,5,[13][14][15][16][17]. Regarding I h specifically, these questions can be summarized in terms of roles: R1: What role does I h have in the existence of a stable HCO rhythm?…”
Section: Leech Heartbeat Case Studymentioning
confidence: 99%